Stem Cell Research in Bangladesh: Neurosurgical Perspective (Bangladesh Journal of Neurosurgery, 2019)
Purpose: Traumatic spinal cord injury (SCI) is a severe neurological disease which causes sensory loss, motor paralysis and autonomic difficulties which is usually treated with physiotherapy. Complete spinal cord injury with ASIA Grade A patients remains untreated and neglected in our country since long back. Here we describe an effective strategy for the treatment of complete spinal cord injury by autologous bone marrow derived stem cell.Material and Method: The study was conducted in the Neurosurgery department, Dhaka Medical College Hospital, Dhaka, Bangladesh from January, 2016 to January 2019. Total 22 Patients with spinal cord injury (ASIA Grade-A) were included in this study. Total 60 ml of autologous bone marrow was aspirated and processed to prepare 6-7 ml of bone marrow aspirate concentrate (BMAC) which was transplanted at the site of cord injury. Bony alignment was done by decompression and stabilization. Post-surgical physiotherapy and regular follow up was given.Result: Surgical outcome was assessed by ASIA Grading. Among 22 patients, 10 patients (45.45%) improved by one grade, 7 patients (31.82%) improved by two grade, 2 patients (9.09%) improved by three grade, 3 patients (13.64%) did not show any improvement of any grade as because their follow-up period was less than 6 months. 19 patients (86.36%) noticed sensory, 16 patients (72.72%) noticed bladder improvement and 19 patients (86.36%) noticed bowel improvement to some extent.Conclusion: Stem cell therapy is safe and effective. Steady and focused progress in stem cell research will open the door for many disable patients in the country like Bangladesh.Bang. J Neurosurgery 2019; 9(1): 3-10